Erythrocytes : Physiology and pathophysiology - Lang, Florian; Föller, Michael (Imperial College Press, 2012)
This authoritative volume explores the functional significance, life cycle, and pathology of erythrocytes, covering their generation, senescence, and suicidal death (eryptosis), as well as hormonal regulation, and disorders such as anemia, malaria and sepsis.